Jeffrey, James. Paprika Paradise: Travels in the Land of my Almost Birth. Sydney: Hachette Australia, 2007. 270 pp. - Kolos, Lilla (FOCUS: Papers in English Literary and Cultural Studies, 2008)
In 2007, Hachette Australia published the first volume of prose by Australian journalist, James Jeffrey. Paprika Paradise, belonging to the genre of travel writing, turned out to be a modest hit in the Australian book market, selling about four thousand copies the first twelve months after publication. Hungarian expatriates formed its main reading public, with their interests propelled by a mixture of nostalgia and a craving for information about today’s Hungary.